Вы находитесь на странице: 1из 13

# Matrix Inversion Formula

## EE 521 Analysis of Power Systems

Chen-Ching Liu
Washington State University
1. Sherman-Morrison-Woodbury Formula:
Let ML(R
n
) be invertible and let U, V be nm
(mn) matrices. Then (M+UV
T
) is invertible if
and only if (I+V
T
M
-1
U) is invertible, and:

To prove (1), we simply pre-multiply and post-
multiply (M+UV
T
) with its inverse matrix to check
whether the result is an identity matrix.

Let H=(I+V
T
M
-1
U)
-1
, then

) 1 ( M V U) M V (I U M - M ) UV (M
-1 T
-1
H
-1 T -1 -1 -1 T

_
+ = +
a) Pre-multiplication

b) Post-multiplication

| |
( ) | |
I M V H H I U I
M V H U M V I I U I
M V UH M V H I U I
M UHV M UV M UHV MM M UV MM
T
I
T T
T T
T T T
I
T
=
(

+ =
+ + =
+ =
+ =
(
(

+ +

1 1
1 1
1 1
1 1 1
1
1 1
1 - T
1 -
H
1 - T 1 - 1 - T
M V U) M V (I U M - M ) UV (M
_
_
| |
( ) | |
| | I V HH I U M I
V U M V I H I U M I
V U M HV H I U M I
UV M UHV M M M UHV M UV M M M
T
T T
T T
T T T T
= + =
+ + =
+ =
+ =
+
(
(

+

1 1
1 1
1 1
1 1 1 1 1 1
T 1 - T
1 -
H
1 - T 1 - 1 -
) UV (M M V U) M V (I U M - M
_
2. Sherman-Morrison Formula:
In eq. (1), if m=1, i.e., U and V are column
vectors, let u and v (u,v R
n
) represent these two
vectors, then let equation (1) can be simplified:

3. Special Case:
Suppose M is symmetrical and M
-1
is known; and
in (2) we have uv
T
=aa
T
, where is a scalar and
a is an n-vector, then (2) becomes:

where:
( )
( )
) 2 (
1
1
1 1
1
1
1

+
= + M uv M
u M v
M uv M
T
T
T
) 3 (
1

_
T
rank
T
bb M aa M =
(
(

+

( )
1
1
1

+ =
=
b a
a M b
T

Example 1: Given

Let

Find M
1
-1
Solution: Here =2 and a=[0 1 0]
T
, So
b=M
-1
a=[-1 2 1]
T
=(
-1
+a
T
b)
-1
=0.4
Use(3)

The result can be verified by direct
multiplication.
(
(
(

=
(
(
(

=
3 2 1
2 2 1
1 1 1
M
1 1 0
1 2 1
0 1 2
1 -
M

| |

T
a
M M 0 1 0
0
1
0
2
1 1 0
1 4 1
0 1 2
(
(
(

+ =
(
(
(

=

| |
(
(
(

=
(
(
(

(
(
(

4 . 1 4 . 0 2 . 0
4 . 0 4 . 0 2 . 0
2 . 0 2 . 0 6 . 0
2 2 1
2
2
1
4 . 0
3 2 1
2 2 1
1 1 1
1
1
M
(M+UV
T
) is a modification of M. Since M
-1
is
assumed known, the inverse of this modified
matrix can be performed without inverting an
nn matrix again. Instead, the necessary
matrix inversion is only for an mm matrix.
When m=1 (Eqs. (2-3)), the matrix inversion
requires only matrix multiplications and matrix

The admittance matrix is symmetrical, and its
change can be easily represented by finding
a vector and a scalar . The corresponding
computational efforts is lower.
a
5. Inverting Admittance Matrix When Line
Suppose that we have Y
bus
and its inverse Z
bus
.
Suppose that the admittance of the k-th branch
connecting node i and node j is changed from y
k

To y
k
+ y
k
. Let to be the new admittance
matrix. We need to find its inverse, .

First, we try to find a vector and scalar
k
.
There are 2 cases to consider:
Case 1: Neither node i nor node j is the reference
node. Then we get the new admittance matrix:

i line k j

Ref.
new
bus
Z
new
bus
Y
k
a

Thus in we can put 1 in the i-th row and 1 in the
j-th row. All other entries are zero. Also
k
= y
k
.
| |
T
k k bus
bus
bus
new
bus
a a Y
Y
Y Y
k
k
k k
k k
y
1 - 1
1
1
y

y y -

y - y

+ =
(
(
(
(
(
(

+ =
(
(
(
(
(
(

+ =
. . .

k
a
Case 2: The k-th branch connects the i-th node to the
reference node. Similar to case 1, we can put a
1 in the i-th row of , and put all other entries
zero. Also we have
k
= y
k
.
i line k Ref

Now we consider calculation of . We already have
Z
bus
=[Y
bus
]-1
. By eq. (3) we obtain:

where

k
a
new
bus
Z
(4) ) ( ) (
1 1

T
k k k bus
T
k k k bus
new
bus
new
bus
b b Z a a y Y Y Z = + = =

(5)
1

(

=
=
k
T
k
k
k
k bus k
b a
y
a Z b

## Let the i-th and the j-th columns of Z

bus
be Z
i
and Z
j
,
respectively, and the ii-th, jj-th, and ij-th elements be
Z
ii
, Z
jj
, and Z
ij
, respectively. According to the two
cases above, Eq. (5) can be simplified:

Case 1: by Eq. (5):

(6)

Case 2: j is the reference node:

(7)

| |
| | | |
1
2
1
1 1
1
1

|
|
.
|

\
|
+ +

=
=
=
(
(
(
(
(
(

=
ij jj ii
k
k
j i k
T
k
j i j i k
z z z
y
Z Z T b a
Z Z Z Z b

. . .

. . .

1
(

=
=
ii
k
k
i k
z
y
Z b

## Example 2: Suppose that for a given network we already have

The network is shown in the figure.

(all values are line admittances p.u.)
( to are branch number)

Note that at the beginning there are no connections between node 1
and node 2. Now we add a line (branch number 5)
between node 1 and node 2. The line admittance is j10.
Find:

(
(
(

=
(
(
(

=
2 . 0 2 . 0 1 . 0
2 . 0 5 . 0 1 . 0
1 . 0 1 . 0 2 . 0
3
and
30 10 10
10 10 0
10 0 20
j
Z j Y
bus bus
-j10 -j10
-j10
-j10
2
3 Ref.
1
1
2
5
4
3
1 5
new
bus
Z
Solution: The change of the admittance of branch 5
y
5
=-j10-j0=-j10

Since neither node 1 nor node 2 is the reference,
we use Eq. (6).

75 . 3 )) 2 . 0 5 . 0 2 . 0 (
3 10
1
(
) 2
1
(
1 . 0
4 . 0
1 . 0
3
2 . 0
5 . 0
1 . 0
1 . 0
1 . 0
2 . 0
3
1
1
12 22 11
5
5
2 1 5
j
j
j
z z z
y
j j
z z b
= + +

=
+

=
(
(
(

(
(
(

(
(
(

= =

## Then by using equation (4):

We can also get directly from the figure:

To check the result, one can simply multiply with

| |
(
(
(

=
(
(
(

(
(
(

=

(
(
(

+ =
=
1875 . 0 1500 . 0 1125 . 0
1500 . 0 3000 . 0 1500 . 0
1125 . 0 1500 . 0 1875 . 0
3

01 . 0 04 . 0 01 . 0
04 . 0 16 . 0 04 . 0
01 . 0 04 . 0 01 . 0
3
25 . 1
2 . 0 2 . 0 1 . 0
2 . 0 5 . 0 1 . 0
1 . 0 1 . 0 2 . 0
3

1 . 0 4 . 0 1 . 0
3
1 . 0
4 . 0
1 . 0
3
75 . 3
j
j
j
j j
j Z
b b Z Z
bus
T
k k k bus
new
bus

new
bus
Z
new
bus
Y
new
bus
Y
(
(
(

=
30 10 10
10 20 10
10 10 30
j Y
new
bus